Receipt of pharmacotherapy for alcohol use disorder by justice-involved women in the Veterans Health Administration - Emmeline Taylor (Addiction Science & Clinical Practice, 2019)
Abstract Background Alcohol use disorder (AUD) and unhealthy drinking are prevalent among women involved in the criminal justice system and women military veterans. Pharmacotherapy—including naltrexone, topiramate, acamprosate, and disulfiram—for AUD is one form of effective treatment that is associated with better health and criminal justice outcomes. The current study examined the association of justice involvement with receipt of pharmacotherapy for AUD, as well as other patient factors that may explain variation in receipt of pharmacotherapy for AUD among women veterans who receive care at Veterans Health Administration (VHA) facilities. Methods Using national VHA clinical records, we examined all women VHA patients who received an AUD diagnosis during an outpatient or inpatient visit in fiscal years (FY) 2014–2017. We compared patient characteristics by justice status, defined as contact with one of the VHA’s justice outreach programs, and used a mixed-effects logistic regression model to test whether justice involvement was independently associated with odds of receiving pharmacotherapy for AUD. Results Of 10,511 women veterans diagnosed with AUD in FY2017, 852 (8%) met our definition of justice-involved. Since FY2014, the percentage of women veterans who received pharmacotherapy for AUD increased (14–21%). Women justice-involved veterans and those who were homeless had higher odds of receiving pharmacotherapy for AUD (OR 1.29, CI 1.15–1.45; OR 1.35, CI 1.25–1.47). Women veterans age 55 or older or who were African-American had lower odds of receiving pharmacotherapy (OR 0.74, CI 0.67–0.82; OR 0.73, CI 0.68–0.79). Conclusions While women involved in the criminal justice system face many barriers to accessing health and social services, women justice-involved veterans had higher odds of receiving pharmacotherapy for AUD at VHA facilities compared to women veterans with no justice involvement. Legal mandates and supportive programming directed towards veterans in the criminal justice system may explain the higher rate of receipt of pharmacotherapy observed among justice-involved women veterans. Women veterans who are homeless may also have more opportunities to access and use pharmacotherapy for AUD compared to their housed counterparts.